Articulating diversity, decoding polarization: Online responses to coca cola’s memleket advertisement - (:unkn) unknown (Peter Lang Publishing Group, 2019)
“We are meeting at the same table in this Ramadan with all our differences and common points, '#enjoy’ "1, the striking slogan by Coca Cola was released with a new advertisement, Memleket Apartmanı (The Hometown Apartment) just before the Muslim holy month of Ramadan. The advertisement portrayed the representations of individuals belonging to different social classes in Turkey. Memleket Apartmanı, which is a metaphor employed by the brand to point at the nation as a whole, has been depicted as a setting which brings together a variety of individuals, including families of conservative/religious lifestyles to secular ones. All these families and individuals were enjoying the fasting month by preparing a shared dinner for themselves, each bringing in a meal to share on the same table. Not surprisingly, the only product identified as a central agent in this union has been the Coca Cola itself, maintaining a crucial position in the table’s orientation, close to everybody attending this unique cultural experience. Challenging the cultural boundaries that distance different lifestyles in Turkey’s contemporary cultural setting, most especially the religious/conservative-oriented lifestyles and secular ones, Coca Cola manifested itself as a perfect commodity that erodes those boundaries and establish the unity of the people altogether. How does Coca Cola manage to establish itself such a unifying position? And how? By which tools provided by the discursive strategies of advertising? What are the mechanisms by which this brand manages to utilize its central slogan, “enjoy!", as a solution…. © Peter Lang GmbH.